Effect of Tungsten-Inert-Gas Preheating on Mechanical and Microstructure Properties of Friction Stir Welded Dissimilar Al Alloy and Mild Steel - Bang, HanSur; Bang, HeeSeon; Na, M.-J.; Jeon, G.-H.; Kim, G.-S.; Kaplan, A.F.H. (Проблемы прочности, 2016)
The purpose of this study is to clarify the effect of tungsten-inert-gas (TIG) welding preheating on the mechanical properties of Al6061-T6 and SS400 welded joints by friction stir welding (FSW). FSW joints with and without TIG welding preheating are characterized and compared in terms of their mechanical and microstructural properties. The results show that the TIG assisted hybrid FSW welded joints (TIG-HFSW) provide an enhanced joint strength. The transversal tensile strength of the TIG-HFSW joints exhibited approximately 104% of the Al6061-T6 base metal tensile strength and was higher than that of the FSW joints. Microstructural investigations also reveal that in the HAZ and TMAZ of TIG-HFSW joints, the grains of Al6061-T6 are smaller than those of the FSW welds.